CC4, a dimer of cytisine, is a selective partial agonist at α4β2/α6β2 nAChR with improved selectivity for tobacco smoking cessation. (24th January 2013) - Sala, Mariaelvina; Braida, Daniela; Pucci, Luca; Manfredi, Irene; Marks, Michael J; Wageman, Charles R; Grady, Sharon R; Loi, Barbara; Fucile, Sergio; Fasoli, Francesca; Zoli, Michele; Tasso, Bruno; et al.
Abstract : Background and Purpose: Many of the addictive and rewarding effects of nicotine are due to its actions on the neuronal nicotinic ACh receptor (nAChR) subtypes expressed in dopaminergic mesocorticolimbic cells. The partial agonists, cytisine and varenicline, are helpful smoking cessation aids. These drugs have a number of side effects that limit their usefulness. The aim of this study was to investigate the preclinical pharmacology of the cytisine dimer1, 2‐bis N ‐cytisinylethane (CC4). Experimental Approach: The effects of CC4 on nAChRs were investigated using in vitro assays and animal behaviours. Key Results: When electrophysiologically tested using heterologously expressed human subtypes, CC4 was less efficacious than cytisine on neuronal α4β2, α3β4, α7 and muscle‐type receptors, and had no effect on 5‐hydroxytryptamine3 receptors. Acting through α4β2 and α6β2 nAChRs, CC4 is a partial agonist of nAChR‐mediated striatal dopamine release and, when co‐incubated with nicotine, prevented nicotine's maximal effect on this response. In addition, it had low affinity for, and was less efficacious than nicotine and cytisine on the α3β4 and α7‐nAChR subtypes. Like cytisine and nicotine, CC4‐induced conditioned place preference (CPP), and its self‐administration shows an inverted‐U dose–response curve. Pretreatment with non‐reinforcing doses of CC4 significantly reduced nicotine‐induced self‐administration and CPP without affecting motor functions. Conclusion and Implications: Our in vitro and in vivo findings reveal that CC4 selectively reduces behaviours associated with nicotine addiction consistent with the partial agonist selectivity of CC4 for β2‐nAChRs. The results support the possible development of CC4 or its derivatives as a promising drug for tobacco smoking cessation.